(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Uvaria chamae roots are traditionally used in the treatment of diabetes in many parts of the world, but the use of the extracts in the treatment of diabetes has not been scientifically validated. Thirty-six Sprague Dawley rats were assigned by weight into six groups [6 rats per group, average body weight 265.23 ± 7.20g]. Diabetes mellitus was induced by a single administration of streptozotocin (60 mg/kg) intraperitoneally. Normal and diabetic rats were treated with aqueous or ethanolic extract (300 mg/kg body weight/day/rat) of Uvaria chamae for 35 days. Rats were allowed free access to food, and extract added to the water bottle. Animals were euthanized on day 35 after an overnight fast and blood was collected for glucose, renal function, liver, serum lipid profile, and inflammatory markers assays. The blood glucose levels decreased by 38% and 53% in the diabetic rats administered aqueous or ethanolic extract respectively compared to an increase in the diabetic control (45%). The levels of TC, TG, LDL-C, VLDL-C, TG/HDL-C, and non-HDL-C were decreased in untreated rats, while the HDL-C was increased when the extracts were administered. There was a diminishing trend in IL-6, TNF-α and IL-1β levels in the treated diabetic groups. Serum creatinine level was slightly elevated in the diabetic group administered ethanolic extract. Overall, the consumption of Uvaria chamae extracts lowered blood glucose levels, lipid profile and increased HDL-C, while the IL-6 was decreased. The non-significant changes in renal function parameters indicated no adverse effects on the kidney in this short-term study.